Fake It to Make It? Emotional Labor Reduces the Racial Disparity in Service Performance Judgments. (May 2019) - Grandey, Alicia A.; Houston, Lawrence; Avery, Derek R.
Service providers who are Black tend to be evaluated less favorably than those who are White, hindering opportunities for advancement. We propose that the Black-White racial disparity in service performance evaluations is due to occupational-racial stereotype incongruence for interpersonal warmth and that more emotional labor is necessary from Blacks to reduce this incongruence. A pilot study manipulating employee race and occupation confirmed warmth and person-occupation fit judgments are lower for an otherwise equal Black than White service provider. We then demonstrate the racial disparity in service performance is due to interpersonal warmth differences in an experimental study with participants evaluating videos of retail clerks (Study 1) and a multisource field study of grocery clerks with supervisor-rated judgments (Study 2). Furthermore, White service providers are rated highly regardless of emotional labor, but performing more emotional labor (i.e., amplifying positive expressions) is necessary for Black providers to increase warmth judgments and reduce the racial disparity. In other words, Black providers are held to a higher standard where they must "fake it to make it" in service roles. We discuss implications for stereotype fit and expectation states theory, emotional labor, and service management.